Niches for bioelectrochemical systems on the recovery of water, carbon and nitrogen in wastewater treatment plants. (November 2019) - Osset-Álvarez, Miguel; Rovira-Alsina, Laura; Pous, Narcis; Blasco-Gómez, Ramiro; Colprim, Jesús; Balaguer, M. Dolors; Puig, Sebastià
Abstract: Climate change and future depletion of resources are two of the most important environmental challenges that humankind have ever faced. This mini-review aims to give a second chance to contaminated water and recalcitrant carbon dioxide (CO2 ) streams by putting forward a resilience and sustainable technology based on electron-driven microbial reactions. A critical assessment of the current application of microbial electrochemical technologies (METs) in the field of electro bioremediation of contaminated water and bio-electro CO2 recycling in wastewater treatment plants (WWTPs) is performed. Data from lab-scale and pilot-plant studies is shown to prove that MET is a highly promising and cost-effective technology for the sustainable remediation of contaminated sites while producing biofuels and/or commodity chemicals from recalcitrant CO2 streams emitted in WWTPs. Graphical abstract: Image 1 Highlights: MET integration within WWTPs shows potential to become a resource refinery. CO2 emissions at WWTP can be reduced using METs while valuable compounds are produced. Water recovery in WWTPs is enhanced by using MET for NH4 + and NO3 − removal. MET can be used for the recovery of NH4 + from ammonium-rich water streams. Integration rather than substitution is essential to attain the best configuration.